PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL THINK PAIR SQUARE UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIIIA SMP NEGERI 1 BENAI - Annisa Nanda Zulia; Kartini '; Susda Heleni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was based on the students math ability class VIIIA of SMPN 1 Benai under the Mastery Minimum Criteria with a percentage of 43,5%,of the Basic Competence 1.2 outlines the algebra into the factors and the learning process still teacher center. The research conducted was the Classroom Action Research. The aims of this research is to improve the learning process and results on the students learning mathematic by implementing cooperative learning model structural approach of Think Pair Square. There were 23 students in the class consisting 15 boys and 8 girls as the participant of this research. The instruments of data collection in this research were observation sheets and students Mathematic tests. The observation sheets were analyzed in qualitative desciptive, while the students’ Mathematic tests were analyzed in quantitative desciptive. The qualitative desciptive showed an improvement of learning process prior to the action on the first and second cycles. Number of students that reach Minimum Mastery Criteria increase from basic score to daily test II. The number of students who reach Minimum Mastery Criteria on basic scor, daily test I and daily test II are respectively 10 person (43,5%), 12 person (52,2%) and 27 person (73,9%). Based on the result of this research could be concluded that the implementation of Cooperative Learning Model structural approach of Think Pair Square can improve the learning process and result on the students’ achievement of learning Mathematic in grade VIIIA of SMPN 1 Benai in the first semester academic years 2016/201, of the basic competence 1.3 Understanding relations and functions. 1.4 Determine the value of functions, and 1.5 Sketching graph of simple algebraic function on the Cartesian coordinate plane.